Penerapan Konsep Trust of Land Dalam Sistem Hukum Agraria: Suatu Perbandingan Hukum Antara Indonesia dan Britania Raya - Oemar Moechthar; Ardian Firmansyah Arifin (Media Iuris, 2022)
AbstractWhen we are talking about the use of land in Indonesia, as an agricultural country, Indonesia has many talented individuals who are more than capable of managing and cultivating the land. Unfortunately, most of these gifted people do not own the land themselves. Indeed, it is not because they do not want to, but because most land already has its owner. On the other hand, there are numerous unused and neglected lands in Indonesia on which the owner cannot manage and cultivate the land themselves. Such an unfortunate situation causes the purpose of the land to achieve prosperity and welfare for the common good of the people to be a meaningless cliché and practically unachievable. For the same situation, the United Kingdom has a concept of land management called the trust of land. This article aims to identify whether the legislators can adopt this concept into the sphere of Indonesian agrarian law where this adoption might achieve the aim of common welfare within Law Number 5 of 1960. This article will provide a conceptual illustration and advice to the legislators to minimise the number of unused and neglected land in Indonesia to actualise Article 33 Clause (3) of the Constitution for the land to be used for the most benefits of the people. Keywords: Control of Neglected Lands; Trust of Land; Land Law Comparison; Bank of Lands. AbstrakBanyaknya tanah-tanah telantar yang ada di penjuru Republik Indonesia membuat tujuan penggunaan dan pemanfaatan sumber daya agraria untuk menciptakan kemakmuran dan kesejahteraan bagi seluruh rakyat Indonesia tidak tercapai. Dalam satu sisi, banyak rakyat yang tidak memiliki tanah untuk digarap bahkan untuk ditinggali, padahal mereka merupakan bagian dari bangsa Indonesia. Melihat kondisi di atas, Britania Raya memiliki konsep pengelolaan lahan yang bernama trust of land. Tujuan dari penulisan artikel ini yakni apakah legislator Indonesia dapat mengadopsi konsep trust of land ke dalam sistem hukum agraria di Indonesia, sehingga pemanfaatan sumber daya agraria dapat lebih memberikan manfaat dan berkelajutan seperti yang diharapkan dari ketentuan Undang-undang No. 5 Tahun 1960. Tujuan dari penulisan artikel ini yakni memberikan gambaran serta masukan kepada legislator dalam upaya meminimalisir tanah-tanah terlantar yang ada di Wilayah Republik Indonesia agar dapat dimanfaatkan untuk sebesar-besar kemakmuran rakyat sebagaimana tertuang dalam ketentuan Pasal 33 ayat (3) Konstitusi Indonesia. Kata Kunci: Pengendalian Tanah Terlantar; Trust of Land; Perbandingan Hukum Agraria; Bank Tanah.